Dr. B.R. AMBEDKAR’S VISION ON EDUCATION - Gasti, Kakasaheb Laxman (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Dr. Bhim Rao Ambedker established People‟s Education Society in Bombay and Aurangabad to educate the students belonging to Depressed classes and backward classes. His educational philosophy is reflected in his lectures, published articles in various magazines and works. He was of the opinion that every educational establishment should be a source to change social structure. He firmly detained that education should be, of main concern for the society and to promote for growth of individuals. In this paper an attempt is made to explore educational thoughts of Dr. Ambedkar, who aimed for a type of education that not only inculcates consciousness and attainment of human rights among citizen but also should teach human dignity and justice. To him Education is the means to oppressed ones to fight against injustice and exploitation they have been suffering from ages. He considers, lack of education as the main cause for the backwardness of women and common men. In this article an attempt is made to assess the contributions of Dr.B.R.Ambedkar to the field educational and to explore the changes in life style of marginalised section through Dr. B. R. Ambedkar’spersonal influence and contribution to the field of Education. The study was conducted based on works of Dr Ambedkar. Mathod adopted is historical and analytical, It is based on analysis of concepts and synthesizing of ideas and evidence drawn from various sources